A provably secure anonymous authentication scheme for Session Initiation Protocol. Issue 18 (27th October 2016) - Chaudhry, Shehzad Ashraf; Khan, Imran; Irshad, Azeem; Ashraf, Muhammad Usman; Khan, Muhammad Khurram; Ahmad, Hafiz Farooq
Abstract: Recently, Lu et al . presented a mutual authentication scheme for Session Initiation Protocol. Lu et al . claimed their scheme provides safeguard against familiar attacks and offers efficient authentication facility. However, this paper divulges that the scheme of Lu et al . is prone to server and user impersonation attacks. Additionally, the scheme of Lu et al . implicates correctness concerns. Consequently, an enhanced scheme is proposed, not only to resolve correctness concerns but also to provide robustness against server and user impersonation attacks. The proposed scheme makes use of a user‐specific secret parameter to deal with the security and correctness issues. The formal and informal security analysis proves the robustness and efficiency of the proposed scheme against all familiar attacks. Furthermore, security analysis is also substantiated through popular automated toolPROVERIF . Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, we have proposed a password‐based authentication scheme using ECC. Formal and informal security analysis confirms the robustness of proposed scheme. The security of proposed scheme is also validated using the popular automated tool ProVerif.